2020
DOI: 10.3389/fonc.2020.549850
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation in Esophageal Squamous Cell Carcinoma: Biological and Clinical Implications

Abstract: Almost all cancer cells possess multiple epigenetic abnormalities, which cooperate with genetic alterations to enable the acquisition of cancer hallmarks during tumorigenesis. As the most frequently found epigenetic change in human cancers, aberrant DNA methylation manifests at two major forms: global genomic DNA hypomethylation and locus-specific promoter region hypermethylation. It has been recognized as a critical contributor to esophageal squamous cell carcinoma (ESCC) malignant transformation. In ESCC, DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 90 publications
3
11
0
Order By: Relevance
“…We identified 369,119 NC-DMCs and 69,439 ESCC-DMCs from the WGBS data covering 18 million CpGs, accounting for 2.44% of the total CpG sites, close to the previously reported 2.7% of methylated CpG sites [27]. Previous studies based on LINE-1, an alternative indicator of the whole genome, consistently observed genome-wide hypomethylation in ESCC [35]. Similar results were obtained in this study, with more NC-DMCs identified than ESCC-DMCs (approximately five times), suggesting the prevalent hypomethylation events in ESCC.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We identified 369,119 NC-DMCs and 69,439 ESCC-DMCs from the WGBS data covering 18 million CpGs, accounting for 2.44% of the total CpG sites, close to the previously reported 2.7% of methylated CpG sites [27]. Previous studies based on LINE-1, an alternative indicator of the whole genome, consistently observed genome-wide hypomethylation in ESCC [35]. Similar results were obtained in this study, with more NC-DMCs identified than ESCC-DMCs (approximately five times), suggesting the prevalent hypomethylation events in ESCC.…”
Section: Discussionsupporting
confidence: 79%
“…The subsequently identified 733 NC-DMGs and 906 ESCC-DMGs included PAX1 [36] and STK3 [37], of which both have been attempted as diagnostic markers for ESCC. Functional enrichment results revealed that ESCC-DMGs enriched in multiple biological processes, such as the reported cell cycle regulation and Wnt signaling pathways [35]. Notably, the top 3 enriched families, NKL subclass homeoboxes and pseudogenes, HOXL subclass homeoboxes and Zinc fingers, were frequently observed hypermethylated in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…It can play an oncogenic role by blocking DNA synthesis in tumor epithelial cells and inhibiting the formation and growth of tumor colonies in the tumor stroma, and is commonly expressed in a variety of normal tissues, with roles in regulating cell proliferation, division, migration, adhesion, and growth, but is silently expressed in a variety of It is commonly expressed in many normal tissues and has a role in regulating cell proliferation, division, migration, adhesion, and growth, but is silently expressed or absent in many malignant tissues [ 5 ]. It has been shown that esophageal cancer may be a malignancy with a high frequency of methylation in the promoter region of oncogenes [ 6 ]. Therefore, oncogene methylation detection is expected to play a great role in the early screening, disease diagnosis, and efficacy monitoring of esophageal cancer, but there are few studies on oncogene methylation in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular epidemiological studies found that epigenetic modification, as a bridge between genetic and environmental factors is correlated with EC 10 , 11 . DNA methylation is one of the structures of epigenetic modification, and the expression of both oncogenes and tumour suppressor genes is affected by methylation of DNA 12 14 . Additionally, methylation of DNA, which plays a key role in gene transcription and gene expression, is one of most extensively studied epigenetic alterations.…”
Section: Introductionmentioning
confidence: 99%